National Inventories of Landscapes in Sweden: NILS Inventory 2003–2020 - Henrik Hedenås (Swedish University of Agricultural Sciences, 2025)
The NILS Inventory 2003–2020 is the original NILS landscape monitoring programme, conducted from 2003 to 2020, and encompassed all terrestrial environments in Sweden, including both lowland and alpine areas (lowland until 2018; alpine until 2020). The programme was established to monitor biodiversity across the Swedish landscape and to track long-term changes in the everyday landscape. A central component was to assess changes in landscape composition and structure, and the prerequisites for biodiversity.

In years 2003–2018 data were collected nationwide, from 2019-2020 data collection continued only in alpine areas.

The true coordinates of the permanent sample plots are protected. The coordinates in this dataset are generalised, by randomly offsetting true coordinates with 200-2000 m. See also Additional Information.

The original NILS Inventory has been replaced and extended by five separate inventories specifically adapted to the different landscape types: the NILS Alpine Inventory (initiated 2021), NILS Deciduous Forest Inventory (initiated 2020), NILS Grassland Inventory (initiated 2020), NILS Wetland Inventory (initiated 2023) and the THUF Seashore Inventory (initiated 2012). Data from those inventories will be published in separate datasets and can currently be accessed only directly from the organisation.
Keywords: Samplingevent; Observation; SAMPLING_EVENT; Biological Sciences; Biologi